Synthesis, properties and applications of new (bio)degradable polyester urethanes - Brzeska, J.; Dacko, P.; Janeczek, H.; Janik, H.; Sikorska, W.; Rutkowska, M.; Kowalczuk, M. (Polimery, 2014)
The paper presents a review of studies on the synthesis and selected properties of two types of new (bio)degradable poly(ester urethane)s with soft segments containing telechelic oligoesterdiols: atactic poly([R,S]-3-hydroxybutyrate) (a-PHB) or polylactide (PLA) and/or aliphatic-aromatic copolymer poly(1,4-butylene terephthalate)-co-(1,4-butylene adipate) (BTA). The reported results indicate that poly(ester urethane)s of the first type are susceptible to degradation in a hydrolytic and oxidative environment. When suitably modified, they exhibit potentially biostatic properties, whereas no change in blood parameters after the direct contact with them suggest their hemocompatibility. The second group of poly(ester urethane)s combines the properties of both PLA and BTA polymers used for the preparation of oligoesterdiols, which is advantageous from the viewpoint of mechanical properties and degradation ability, confirmed by biodegradation studies under industrial composting conditions.